Importance of Preventive Dental Care During Antenatal Period in Pregnant Women: A Pakistani Perspective - Nikita Bodani; Shweta Darshan; Abhishek Lal (ziauddin University, 2024)
Dental caries and periodontal diseases are amongst the most common non-communicable diseases globally 1. According to the World Health Organisation (WHO), more than 3.5 billion individuals suffer from one of the many oral diseases, with an economic burden exceeding a total of $387 in both public and private health sectors2. According to the Centers for Disease Control and Prevention, 60-75% of pregnant women suffer from gingivitis, which is mainly due to already poor oral health and hormonal changes3.